The role of upper and lower genital tract microbiota alterations in term chorionamnionitis: A prospective study - Li, Meng; Huang, Zhenyu; Tao, Zhi; Meng, Yiting; Wen, Jia; Zhang, Qiongqiong; Liu, Ying; Shang, Mengyuan; Wang, Ying; Wang, Yufeng; Chen, Rui; Wang, Xiaoqian; et al. (Frontiers in Microbiology, 2022)
Objective This study aimed to compare the dynamics of lower and upper genital tract microbiota in normal term pregnancy, histological chorioamnionitis (HCA), and clinical chorioamnionitis (CCA) patients to provide a reference for the diagnosis and treatment of chorioamnionitis (CAM) patients. Methods We prospectively collected vaginal and cervical secretions, as well as placenta tissues, fetal membranes, and amniotic fluid from normal-term pregnant women, HCA and CCA patients. Then, we performed genomic DNA extraction and PCR amplification for all samples. The eligible samples were analyzed by 16S ribosomal RNA (16S rRNA) sequencing. Additionally, all placenta tissues were histopathologically examined, and neonatal pharyngeal swabs and placenta tissues from the HCA and CCA groups were subjected to microbial culture. Results A total of 85 term pregnant women were enrolled in this study, including 34 in the normal group (N), 37 in the HCA group, and 14 in the CCA group. A total of 171 qualified samples were analyzed by 16S rRNA sequencing. The results suggested that the cervical microbiota was highly similar to the vaginal microbiota in normal term parturients, with Lactobacillus as the dominant bacterium. Moreover, there was no difference in the alpha and beta diversity of vaginal microbiota between the N, HCA, and CCA groups at the genus level. Besides, no significant differences were detected in cervical microbiome among the three groups. Regarding intrauterine microorganisms, the N and HCA groups had similar microbial composition but were different from the CCA group. No microbe was detected in the placental tissue of normal term parturients, while some microorganisms were found in the intrauterine amniotic fluid and fetal membrane samples. Regardless of cultivation or 16S rRNA sequencing, an extremely low microbial positive rate was detected in HCA and CCA intrauterine samples. Compared to the normal group, Lactobacillus was significantly reduced in the CCA group intrauterine, and Ureaplasma and Enterococcus increased with no statistically significant. Conclusion The N, HCA and CCA groups had similar composition of vaginal and cervical microflora. Some normal-term pregnant women can harbor non-pathogenic microbiota in the uterine cavity. Sterile inflammation is more frequent than microbial-associated inflammation in term HCA and CCA parturients.